Respuesta :
Answer:
0
Step-by-step explanation:
[tex]f(x)=\sqrt{x}+12 and g(x)=2\sqrt{x}[/tex]
We need to find (f-g)(144)
(f-g)(144) = f(144) - g(144)
[tex]f(x)=\sqrt{x}+12[/tex]
[tex]f(144)=\sqrt{144}+12=12+12= 24[/tex]
[tex]g(x)=2\sqrt{x}[/tex]
[tex]g(144)=2\sqrt{144}=2(12)= 24[/tex]
(f-g)(144) = f(144) - g(144)= 24-24=0
Answer:
o is correct answer
Step-by-step explanation:
f(x)=[tex]\sqrt{x}[/tex]+12
g(x)=2[tex]\sqrt{x}[/tex]
we will find
(f-g)x=[tex]\sqrt{x}[/tex]+12-2[tex]\sqrt{x}[/tex]
(f-g)x=-[tex]\sqrt{x}[/tex]+12
now we will find
(f-g)(144)
put x=144
(f-g)(144)=- [tex]\sqrt{144}[/tex]+12
(f-g)(144)=-12+12=0
hence proved